The COVID‐19 Pandemic Not Only Poses Challenges, but Also Opens Opportunities for Sustainable Transformation. Issue 7 (20th July 2021) - Pradhan, Prajal; Subedi, Daya Raj; Khatiwada, Dilip; Joshi, Kirti Kusum; Kafle, Sagar; Chhetri, Raju Pandit; Dhakal, Shobhakar; Gautam, Ambika Prasad; Khatiwada, Padma Prasad; Mainaly, Jony; Onta, Sharad; Pandey, Vishnu Prasad; et al.
Abstract: The COVID‐19 pandemic has impacted social, economic, and environmental systems worldwide, slowing down and reversing the progress made in achieving the Sustainable Development Goals (SDGs). SDGs belong to the 2030 Agenda to transform our world by tackling humankind's challenges to ensure well‐being, economic prosperity, and environmental protection. We explore the potential impacts of the pandemic on SDGs for Nepal. We followed a knowledge co‐creation process with experts from various professional backgrounds, involving five steps: online survey, online workshop, assessment of expert's opinions, review and validation, and revision and synthesis. The pandemic has negatively impacted most SDGs in the short term. Particularly, the targets of SDG 1, 4, 5, 8, 9, 10, 11, and 13 have and will continue to have weakly to moderately restricting impacts. However, a few targets of SDG 2, 3, 6, and 11 could also have weakly promoting impacts. The negative impacts have resulted from impeding factors linked to the pandemic. Many of the negative impacts may subside in the medium and long terms. The key five impeding factors are lockdowns, underemployment and unemployment, closure of institutions and facilities, diluted focus and funds for non‐COVID‐19‐related issues, and anticipated reduction in support from development partners. The pandemic has also opened a window of opportunity for sustainable transformation, which is short‐lived and narrow. These opportunities are lessons learned for planning and action, socio‐economic recovery plan, use of information and communication technologies and the digital economy, reverse migration and "brain gain, " and local governments' exercising authorities. Plain Language Summary: The current pandemic has impacts on social, economic, and environmental systems, including Sustainable Development Goals (SDGs). SDGs consist of 17 interlinked goals that aim to achieve a better and more sustainable future for all. We studied the pandemic's impacts on SDGs for Nepal by following a knowledge co‐creation process. For this, we conducted online surveys and workshops with experts from various professional backgrounds and assessed expert's opinions articulated in the surveys and workshops. The experts reviewed and validated our assessment. Then, we revised and synthesized the assessment. Our study highlights that the pandemic has negatively impacted most SDGs, particularly the targets of SDG 1, 4, 5, 8, 9, 10, 11, and 13. These negative impacts may subside in the medium and long terms. The key factors behind the negative impacts are: lockdowns, underemployment and unemployment, closure of facilities, diluted focus and funds for non‐pandemic issues, and anticipated reduction in development support. The pandemic has also opened a short‐lived and narrow window of opportunity for sustainable transformation. The transformative opportunities consist of lessons learned for planning and actions, socio‐economic recovery plan, use of information and communication technologies and the digital economy, reverse migration and "brain gain, " and local governments' exercising authorities. Key Points: The COVID‐19 pandemic has negative impacts on most Sustainable Development Goals, which may subside in the medium and long terms Key impeding factors causing the negative impacts include lockdowns, unemployment, and diluted focus on non‐COVID‐19‐related issues The COVID‐19 pandemic has also opened a short‐lived and narrow window of opportunity for sustainable transformation